Myeloid - derived suppressor cells in Type 1 diabetes are an expanded population exhibiting diverse T-cell suppressor mechanisms - Grohová, Anna; Dáňová, Klára; Adkins, Irena; Šumník, Zdeněk; Petruželková, Lenka; Obermannová, Barbora; Koloušková, Stanislava; Špíšek, Radek; Palová-Jelínková, Lenka (PloS one, 2020)
Myeloid-derived suppressor cells (MDSC) represent a heterogeneous group of immature myeloid cells with immunoregulatory function in cancer and autoimmune diseases. In humans, two subsets of MDSC were determined based on the characteristic surface markers, monocytic MDSC (M-MDSC) and granulocytic MDSC (G-MDSC). Expansion of MDSC has been reported in some murine models and patients with autoimmune diseases and their immune-suppressive properties were characterized. However, the exact role of MDSC in the pathogenesis of autoimmune diseases is more complex and/or controversial. In type 1 diabetes mellitus (T1D), the increased frequency of MDSC was found in the blood of T1D patients but their suppressor capacity was diminished. In our study, we assessed the role of M-MDSC in the pathogenesis of T1D and showed for the first time the increased frequency of M-MDSC not only in the blood of T1D patients but also in their at-risk relatives compared to healthy donors. T1D patients with inadequate long term metabolic control showed an elevation of M-MDSC compared to patients with better disease control. Furthermore, we described the positive correlation between the percentage of M-MDSC and Th17 cells and IFN-γ producing T cells in T1D patients and their at-risk relatives. Finally, we found that the ability of M-MDSC to suppress autologous T cells is efficient only at the high MDSC: T cells ratio and dependent on cell-cell-contact and TGF-β production. Our data show that the engagement of MDSC in the pathogenesis of T1D is evident, yet not entirely explored and more experiments are required to clarify whether MDSC are beneficial or harmful in T1D.
Keywords: diabetes mellitus 1. typu; Male; Interferon-gamma; Adolescent; regulační T-lymfocyty; Child; dítě; interferon gama; mužské pohlaví; Th17 Cells; CD4 Lymphocyte Count; mladiství; počet CD4 lymfocytů; myeloidní supresorové buňky; T-Lymphocytes, Regulatory; lidé; ženské pohlaví; Humans; Diabetes Mellitus, Type 1; Female; buňky Th17; Myeloid-Derived Suppressor Cells